Anatomical study of blood supply to the cervical spinal cord in the guinea pig. (11th December 2014) - Mazensky, David; Danko, Jan; Petrovova, Eva; Flesarova, Slavka; Supuka, Peter; Supukova, Anna; Luptakova, Lenka; Purzyc, Halina
Abstract The aim of this study was to describe the arterial arrangement of the cervical spinal cord in the guinea pig. The study was carried out on 20 adult English self guinea pigs using corrosion and dissection technique. Batson's corrosion casting kit no. 17© was used as a casting medium. The origin of the ventral spinal artery from the left vertebral artery was found on average in 35% of the cases and from the right vertebral artery on average in 40% of the cases. The ventral spinal artery with origin from the anastomosis of two medial branches was found on average in 25% of the cases. The presence of ventral radicular branches of rami spinales entering the ventral spinal artery in the cervical region was observed in 42% of the cases on the right side and in 58% of the cases on the left side. The presence of dorsal radicular branches of rami spinales that reached the spinal cord was observed in 63% of the cases on the left side and in 37% of the cases on the right side. The number of radicular branches supplying the spinal cord is greater in guinea pig than in humans.